Effect of Firm Size on Sales Growth with Capital Structure as An Intervening Variable - Shafarina Dewi Kusuma; Nurika Restuningdiah; Puji Handayati (AIBPM Publisher, 2021)
The increasing need for consumer goods can cause the sectors of consumer goods are trying to increase their production activity which is supported by the firm's performance. It gives a signal of the high level of cash flow in the future and as a positive signal to creditors as an indication of the firm's sales growth. The purpose of this research is to test the validity of trade-off theory and resource-based view theory. In addition, this study aims to determine the direct effect and indirect effect between firm size on sales growth through capital structure. The sample used in this study are the sixteen companies for three years and those were tested by using path analysis and uses a quantitative research approach. The results of this study prove that firm size has a significant positive effect on sales growth through capital structure, which is proven based on the comparison of the indirect effect with the direct effect. This study aims to determine the direct effect and indirect effect between firm size on sales growth through capital structure. The sample used in this study is sixteen consumer goods sector companies that are listed on the Indonesia Stock Exchange throughout 2016-2018. Sixteen companies were tested using path analysis. The result of this study shows that firm size has a significant positive effect on sales growth through capital structure, which is proven based on the comparison of the indirect effect with the direct effect.